Efektivitas Pendalaman Alkitab dalam Membentuk Karakter Kristiani Naposo Bulung di Gereja HKI Resort Khusus Sidikalang Kota - Christin I G Pakpahan; Tiniresa Lumbantoruan; Agnes Novianti Hutahaean; Roarta Agustina Marpaung; Jakaria Nababan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effectiveness of Bible study worship in shaping Christian character among Naposo Bulung (church youth) at HKI Resort Khusus Sidikalang Kota. Field observations revealed that many youth were not fully engaged in worship activities, often distracted by mobile phones, chatting during services, and showing a lack of appreciation for spiritual advice. The research employed a qualitative descriptive method using observation and interviews with active participants of Bible study worship. The results show that Bible study worship significantly contributes to enhancing worship discipline, deepening theological understanding, and developing Christian values such as love, forgiveness, humility, and spiritual responsibility. Despite challenges such as busy schedules and digital distractions, a contextual approach to Bible study effectively addresses both the spiritual and social needs of Naposo Bulung. Therefore, Bible study worship proves to be an effective means of holistic character formation for the church's younger generation—spiritually, morally, and socially. This activity should continue to be developed and adapted to contemporary contexts so that the church can shape resilient young people in faith and Christian character.